16th June: Proper 6: Luke 7:36-50 - Richter, Amy E. (The expository times, 2013)
The article discusses the June 16th gospel from Luke 7:34 verse. It says that the Luke's gospel deals with the dinner of Jesus at the house of Simon the Pharisee. It states that the dinner party was the worst for Simon the Pharisee, in which, Jesus has taught and open the eyes of Simon the Pharisee on a new way of living.